Tramadol and Dexamethasone as Adjuvant to Bupivacaine in Supraclavicular Brachial Plexus Block - Shrutika Ved; Neel Rana; Shruti Shah; Ruchi Shah; Ishitaben Gajipara; Mrugakshi Dave (Saintika Medika)
Background: To assess the effects of combining Tramadol and Dexamethasone with Bupivacaine in supraclavicular brachial plexus block for upper limb surgeries.